Mid-Day Meals Scheme in Hilly Areas: Tamil Nadu, India - Mahendran, A; Indrakant, S (Asian Journal of Agriculture and Rural Development, 2014)
In the year 1956 the state of Tamil Nadu introduced the Mid-Day meals scheme for the first time in the country. Today almost all states are following different methods of menu’s and patterns. The government is trying to solve the problems of malnutrition and other side to concentrate as school education from 1st standard to 10th standard. In the state one step forward to introduce different food menu and importantly to launched daily eggs for children. Aim of this case study to find out the utilisation of mid-day meals programme among school children based on filed visit in children, teacher, organiser, cook, parents and public and also what are problems are faced by school children in hilly, rural and urban areas. Most of the studies concluded that the scheme is working satisfactorily (urban, coastal areas) in Tamil Nadu and even recommend that other states should follow the Tamil Nadu Mid-Day meals scheme. The working of the Mid-Day Meals Scheme in hilly, rural areas was not assessed till now and needs to be examined. This study was conducted at Theni district, Tamil Nadu. This case study concludes that Mid-Day Meals Scheme in Tamil Nadu has positive points and negative points. The children faced many problems and others opinions are not satisfied. However, with some more Commitment, Vision and Realism the Scheme can be made more effective to fulfil the dreams of K. Kamaraj and M.G. Ramachandran. In the case study strongly suggested alarming findings about the future development of Mid-Day Meals programme.